OA36 Bimekizumab in patients with psoriatic arthritis: achievement and maintenance of Psoriatic Arthritis Response Criteria responses through 3 years in a phase 2b open-label extension study. (23rd April 2022) - Tillett, William; McInnes, Iain B; McGonagle, Dennis; Jadon, Deepak R; Ink, Barbara; Assudani, Deepak; Coarse, Jason; Eells, Jason; Coates, Laura C
Abstract: Background/Aims: Bimekizumab (BKZ), a monoclonal IgG1 antibody that selectively inhibits interleukin (IL)-17F and IL17A, has demonstrated an acceptable safety profile with improvements in joint and skin outcomes to 3 years in patients with active psoriatic arthritis (PsA). Psoriatic Arthritis Response Criteria (PsARC) response data can help relate clinical trial data to UK clinical practice. We report PsARC response rates to 3 years in patients with active PsA from the phase 2b 48-week (wk) dose-ranging study BE ACTIVE (NCT02969525) and its open-label extension (OLE)(NCT03347110). Methods: In BE ACTIVE, patients were randomised (1:1:1:1:1) to placebo, BKZ 16mg, BKZ 160mg (with or without 320mg loading dose), or BKZ 320mg, every 4 wks (Q4W). At Wk12, patients assigned to placebo or BKZ 16mg were reassigned (1:1) to dose-blind BKZ 160mg or 320mg Q4W; other patients remained on their original dose. From Wk48 all patients received open-label BKZ 160mg Q4W. We report PsARC to Wk152 and maintenance of response among patients with PsARC response at Wk12, for the full analysis set (FAS). Data are reported as observed and with NRI. Results: 206 patients were randomised at baseline in BE ACTIVE and included in the FAS. 181 patients entered the OLE and 161 completed the OLE. 157 patients had calculable PsARC response at Wk152. At Wk12, PsARC response (NRI) was achieved by 125/206, including placebo: 33.3% (14/42), BKZ 16mg: 56.1% (23/41), 160mg: 73.2% (60/82), 320mg: 68.3% (28/41) (Table). At Wk48 and Wk152, 78.2% (161/206) and 68.0% (140/206) patients were PsARC responders, respectively. Of the 125 PsARC responders at Wk12, 88.8% (111/125) also met PsARC at Wk48 and 74.4% (93/125) were PsARC responders at Wk152 (NRI). Over 152 wks, the exposure-adjusted incidence rate per 100 patient-years was 126.4 for all treatment-emergent adverse events (TEAEs), 4.1 for serious TEAEs, 0.7 for serious infections and 4.6 for Candida infections. Conclusion: A numerically higher proportion of patients achieved PsARC response in all BKZ-treated groups at Wk12, compared with placebo. The PsARC response rate was sustained through 3 years. Nearly three-quarters of patients who achieved PsARC at Wk12 were also PsARC responders at Wk152. No new safety signals were observed. Disclosure: W. Tillett: Consultancies; WT has received consulting fees from AbbVie, Amgen, Celgene, Eli Lilly, Janssen, MSD, Novartis, Pfizer and UCB Pharma. Honoraria; WT has received honoraria from AbbVie, Amgen, Celgene, Eli Lilly, Janssen, MSD, Novartis, Pfizer and UCB Pharma. Grants/research support; WT has received research grants from AbbVie, Amgen, Celgene, Eli Lilly, Janssen, MSD, Novartis, Pfizer and UCB Pharma. I.B. McInnes: Consultancies; IBM has received consulting fees from AbbVie, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, UCB Pharma. Honoraria; IBM has received honoraria from AbbVie, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Eli Lilly, Janssen, Novartis, UCB Pharma. Grants/research support; IBM has received research support from Boehringer Ingelheim, BMS, Celgene, Janssen and UCB Pharma. D. McGonagle: Consultancies; DM has received consulting fees from AbbVie, Celgene, Janssen, Merck, Novartis, Pfizer and UCB Pharma. Honoraria; DM has received honoraria from AbbVie, Celgene, Janssen, Merck, Novartis, Pfizer and UCB Pharma. Member of speakers' bureau; DM has been on speaker's bureau for AbbVie, Celgene, Janssen, Merck, Novartis, Pfizer and UCB Pharma. Grants/research support; DM has received grants/research support from AbbVie, Celgene, Janssen, Merck, Pfizer and Novartis. D.R. Jadon: Consultancies; DRJ has received consultancy fees from AbbVie, Amgen, Biogen, BMS, Celgene, Celltrion, Eli Lilly, Fresenius Kabi, Galapagos, GSK, Janssen, Merck, Novartis, Pfizer, Roche, Sandoz, Sanofi and UCB Pharma. Grants/research support; DRJ has received research grants from AbbVie, Amgen, Biogen, BMS, Celgene, Celltrion, Eli Lilly, Fresenius Kabi, Galapagos, GSK, Janssen, Merck, Novartis, Pfizer, Roche, Sandoz, Sanofi, UCB Pharma. B. Ink: Corporate appointments; BI is an employee of UCB Pharma. Shareholder/stock ownership; BI is a shareholder of GSK and UCB Pharma. D. Assudani: Corporate appointments; DA is an employee of UCB Pharma. Shareholder/stock ownership; DA is a shareholder of UCB Pharma. J. Coarse: Corporate appointments; JC is an employee of UCB Pharma. Shareholder/stock ownership; JC is a shareholder of UCB Pharma. J. Eells: Corporate appointments; JE is an employee of UCB Pharma. Shareholder/stock ownership; JE is a shareholder of UCB Pharma. L.C. Coates: Consultancies; LCC has received consulting fees from AbbVie, Amgen, Biogen, Boehringer Ingelheim, Celgene, Domain, Eli Lilly, Gilead and Janssen. Member of speakers' bureau; LCC has been on speaker's bureau for AbbVie, Amgen, Biogen, Celgene, Eli Lilly, Gilead, GSK, Janssen, Medac, Novartis, Pfizer and UCB Pharma. Grants/research support; LCC has received grants/research support from AbbVie, Amgen, Celgene, Eli Lilly, Gilead, Janssen, Novartis, Pfizer and UCB Pharma.